A new PCR-based approach indicates the range of Clonorchis sinensis now extends to Central Thailand. - Rebecca J Traub; Julie Macaranas; Mathirut Mungthin; Saovanee Leelayoova; Thomas Cribb; K Darwin Murrell; R C Andrew Thompson (Public Library of Science (PLoS), 2009)
Differentiation of the fish-borne trematodes belonging to the Opisthorchiidae, Heterophyidae and Lecithodendriidae is important from a clinical and epidemiological perspective, yet it is impossible to do using conventional coprological techniques, as the eggs are morphologically similar. Epidemiological investigation therefore currently relies on morphological examination of adult worms following expulsion chemotherapy. A PCR test capable of amplifying a segment of the internal transcribed spacer region of ribosomal DNA for the opisthorchiid and heterophyid flukes eggs taken directly from faeces was developed and evaluated in a rural community in central Thailand. The lowest quantity of DNA that could be amplified from individual adults of Opisthorchis viverrini, Clonorchis sinensis and Haplorchis taichui was estimated at 0.6 pg, 0.8 pg and 3 pg, respectively. The PCR was capable of detecting mixed infection with the aforementioned species of flukes under experimental conditions. A total of 11.6% of individuals in rural communities in Sanamchaikaet district, central Thailand, were positive for 'Opisthorchis-like' eggs in their faeces using conventional parasitological detection techniques. In comparison to microscopy, the PCR yielded a sensitivity and specificity of 71.0% and 76.7%, respectively. Analysis of the microscopy-positive PCR products revealed 64% and 23% of individuals to be infected with O. viverrini and C. sinensis, respectively. The remaining 13% (three individuals) were identified as eggs of Didymozoidae, presumably being passed mechanically in the faeces following the ingestion of infected fishes. An immediate finding of this study is the identification and first report of a C. sinensis-endemic community in central Thailand. This extends the known range of this liver fluke in Southeast Asia. The PCR developed herein provides an important tool for the specific identification of liver and intestinal fluke species for future epidemiological surveys.